Tire crumb rubber effect on hot bituminous mixtures fatigue-cracking behaviour - Moreno-Navarro, Fernando; Rubio-Gámez, Maria Carmen; Jiménez Del Barco-Carrión, Ana (Journal of Civil Engineering and Management, 2015)
The use of tire crumb rubber in road engineering as a modifier of bituminous mixes constitutes one of the revalorization techniques for this waste. The main objective of this research consists of analysing the possible fatigue cracking improvements in the performance of bituminous mixtures containing crumb rubber in comparison to bituminous mixtures manufactured with conventional bitumen and bitumen modified with SBS polymers. For this purpose, four different types of mixes with the same mineral skeleton but different bitumens were studied. The test used to evaluate their behaviour was the UGR-FACT with an additional system for taking pictures, which allows controlling the propagation of the cracks at every moment. The results show that the addition of crumb rubber retards the appearance of cracks; however, once it begins, the damage propagation is faster. Therefore, the fatigue cracking life of mixes with crumb rubber seems considerably longer than the fatigue cracking life of those with conventional bitumens. Moreover, in the mixes with crumb rubber added by the dry process, cracks are thinner and less ramified than in the other ones.